STRATEGI PEMBELAJARAN INKUIRI - Yahdi, Muhammad (Inspiratif Pendidikan, 2016)
Inquiry Learning includes in the learning strategy category that emphasizes on the roles and responsibilities of learners in learning. The learners are given the many opportunities to seek, understand, analyze and synthesize by their own ways. This strategy is to understand that every student has the ability to find their own and the basics abilities in every learner can be developed to find information by themselves. Besides the ease of understanding the lessons and other objects in a way where students are directly involved to seek and find. The students’ understanding is the result of the process done by themselves.